THE EFFECT OF GIVING MICORIZA ARBUSCULAR (CMA) AND P FERTILEZER DOSAGE ON GROWTH AND PRODUCTION OF OKRA (Abelmoschus esculentus L) - Roni Novianto; Sri Hartatik (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2021)
Okra is a vegetable crop that has a high selling value and the production of okra is more exported than sold domestically. The demand for okra from year to year continues to increase from various countries, especially Japan, which imports the most okra from Indonesia. Fertilization of phosphorus (P) fertilizer to fulfill nutrients and provision of arbuscular mycorrhizal fungi (CMA) for more efficient and maximum absorption by plants. Phosphorus (P) fertilizer can increase the production and quality of okra. The aim of this study was to determine the combination of treatment of arbuscular mycorrhizal fungi and which dosage of P fertilizer was best to increase the yield of okra production. The design used was a completely randomized design (CRD) with factorial treatment consisting of two factors. The first factor is the dose of arbucular mycorrhizal fungi (CMA) consisting of 4 levels, namely (0; 160; 320; 480) and the second factor is the dose of P fertilizer (75; 100; 125; 150). Parameters observed were plant height, number of leaves per plant, volume of roots, number of fruits per plant, weight of fresh fruit per plant and weight of plant dry corpse. Based on the analysis of variance, it showed that the interaction was significantly different on the variables of root volume, plant height, number of fruits and fruit weight. Based on research, the CMA dose of 320 kg / ha and the dose of 125 kg / ha gave the highest production results.